Impact of Trust on The Willingness to Use E-Government Services - Assegaff, Setiawan; Aryani, Lies; Sunoto, Akwan; Usmayanti, Vivi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
The primary objective of this study was to gain insight into individual perceptions of using online public services offered by local governments. The research aimed to determine how performance expectancy, effort expectancy, trust in government, facilitating conditions, and social influence impact individuals' intentions and behaviors in using online government services. Data were collected using an online questionnaire, and analysis was conducted using structural equation modeling with SmartPLS. The key findings include the positive influences of trust in government and facilitating conditions on users' intentions and behaviors related to e-government services. However, the study did not identify a significant relationship between performance expectancy, effort expectancy, and social influence concerning user intentions and behaviors in using e-government services.